Avaliação do incentivo ao aleitamento materno e seus fatores associados em um banco de leite humano referência em Minas Gerais - Cristianny Miranda e Silva (2016)
Introduction: The Baby Friendly Hospital Initiative, through the "Ten Steps to Successful Breastfeeding" and the human milk banks are characterized as important agents promoting, protecting and supporting breastfeeding. Objective: To investigate the encouragement of breastfeeding upon adherence to steps 3 to 9of the "Ten steps to successful breastfeeding" of the Baby Friendly Hospital Initiativeamong mothers assisted at a Human Milk Bank and its associated factors. Methodology: This was a retrospective study using secondary data obtained from structured care protocol of nursing mothers (2009-2012). Maternal sociodemographic data, information about the pre- and post-pregnancy and data about the newborn and childbirth were evaluated. These variables were related to part of the "Ten Steps to Successful Breastfeeding". A descriptive analysis, the Kolmogorov-Smirnov test, Mann-Whitney test, chi-square test and Cochran-Armitage test were performed. The simple Poisson regression, a Poisson regression with hierarchical approach, and multinomial logistic regression were also performed. Results:12,283 mothers, with a median of 29 (12-54) years old were evaluated. The analysis of educational practices according to the "Ten Steps" demonstrated higher prevalenceof skin to skin contact and breastfeeding in the delivery room (step 4), exclusive breastfeeding (step 6) and breastfeeding on demand (step 8) and use of artificial nipples (step 9) among mothers who received guidance on breastfeeding during prenatal care. The research about the factors associated with guidance on breastfeeding during prenatal care and exclusive breastfeeding among nursing mothers denoted higher prevalence of guidelines among mothers with higher education (bachelor's degree level; PR=3.23, 95%CI 1.09-9.52) and those who had six or more prenatal consultations (OR=1.41, 95%CI 1.08-1.84), unlike those who did prenatal care in the public sector (PR=0.48; 95%CI 0.38-0.60). Furthermore, a higher prevalence of exclusive breastfeeding was noted among mothers who gave birth without complications (OR=1.37, 95%CI 1.24-1.52) and in the Baby Friendly Hospital(PR=1.21; 95%CI 1.07-1.38), those who had term infants (OR=1.49; 95%CI 1.38- 1.60), those who did over 6 prenatal visits (OR=1.58; 95%CI 1.23-2.03) and whose children were not using pacifiers (PR=1.22, 95%CI 1.14-1.30), as opposed to who had caesarean sections (PR=0.80; 95%CI 0.71-0.90). As for the skin to skin contact between mother and child and breastfeeding in the delivery room, a lower prevalence of such practices was identified among mothers whose delivery was performed inmajor hospitals in the capital (PR=0.89, 95%CI 0.82-0.97 and PR=0.41; 95%CI 0.34- 0.49, respectively). As for artificial nipples, a lower chance of using pacifiers and nursing bottles was noted among babies that were born in Baby Friendly Hospitals (OR=0.03; 95% CI 0.02-0.05), breastfed exclusively (OR=0.09; 95%CI 0.07-0.12) and on demand (OR=0.53; 95%CI 0.40-0.71) and among those babies whose mothers were counseled on breastfeeding (OR=0.73; 95%CI 0.57-0.94). Conclusion: The present findings indicate the importance of adhering to the stepsstudied in breastfeeding promotion, as well as the influence of sociodemographic characteristics, pre- and post-pregnancy maternal information and characteristics related to the newborn and childbirth in carrying out of this practice.